Development of sensor system for real-time measurement of droplet deposition of agricultural sprayers - Li, Longlong; Zhang, Ruirui; Chen, Liping; Yi, Tongchuan; Xu, Gang; Xue, Daxuan; Tang, Qing; Hewitt, Andrew John; An, Yining (International Journal of Agricultural and Biological Engineering, 2021)
During the chemical application process, droplet deposition on a target is an important reference indicator for evaluating the spraying technique and its performance. In order to quickly obtain deposition results in the field, this study proposed a novel system based on surface humidity sensors. The basic principle is to convert the measured physical quantity change into a capacitance change, thereby realizing the physical quantity to electrical signal conversion. An Android application for mobile terminal and the corresponding coordinator were developed, which allowed operators to control multiple sensors simultaneously through the Bluetooth. The soluble tracer detected by spectrophotometer was used to calibrate the system. The obtained results indicated a good correlation between deposition volume and voltage increment output from the newly developed system (R2 of the six nozzles with Dv0.5 ranging from 107.28 μm to 396.20 μm were 0.8674-0.9729), and a power regression model based on the least squares technique (R2=0.8022) was developed. In the field test, the system exhibited an optimal performance in predicting the deposition volume. Compared with the conventional method of measuring tracer concentration, the deviation was less than 10%. In addition, the system exhibited good fitting curve of the deposition distribution with droplet number results measured by the water sensitive paper method. Keywords: deposition measurement, agricultural sprayer, droplets, intelligent sensor DOI: 10.25165/j.ijabe.20211405.5528 Citation: Li L L, Zhang R R, Chen L P, Yi T C, Xu G, Xue D X, et al. Development of sensor system for real-time measurement of droplet deposition of agricultural sprayers. Int J Agric & Biol Eng, 2021; 14(5): 19–26.